2015
DOI: 10.1111/plb.12371
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics and related gene expression of after‐ripening on seed dormancy release in rice

Abstract: After-ripening is a common method used for dormancy release in rice. In this study, the rice variety Jiucaiqing (Oryza sativa L. subsp. japonica) was used to determine dormancy release following different after-ripening times (1, 2 and 3 months). Germination speed, germination percentage and seedling emergence increased with after-ripening; more than 95% germination and 85% seedling emergence were observed following 1 month of after-ripening within 10 days of imbibition, compared with <45% germination and 20% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
0
11
0
3
Order By: Relevance
“…The segregation of PHS to normal phenotype in two mutant plants fits the 1 : 3 ratios with probabilities of 0.38 (χ 2 = 0.77 < χ0.05,12 = 3.84) and 0.10 (χ 2 = 2.69 < χ0.05,12 = 3.84) by χ 2 ‐square test, respectively. Dormancy release was ordinarily required for germination of fresh harvest seeds in rice (Du et al ., ; Shu et al ., ). However, seed germination rates (36 h) of fresh harvest from two mutant progeny plants, which did not go through dormancy release, were 23.3% and 26.0%, respectively, and were significant higher than that of the wild‐type (0.7%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The segregation of PHS to normal phenotype in two mutant plants fits the 1 : 3 ratios with probabilities of 0.38 (χ 2 = 0.77 < χ0.05,12 = 3.84) and 0.10 (χ 2 = 2.69 < χ0.05,12 = 3.84) by χ 2 ‐square test, respectively. Dormancy release was ordinarily required for germination of fresh harvest seeds in rice (Du et al ., ; Shu et al ., ). However, seed germination rates (36 h) of fresh harvest from two mutant progeny plants, which did not go through dormancy release, were 23.3% and 26.0%, respectively, and were significant higher than that of the wild‐type (0.7%) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…japonica ) was used from the Taihu Lake valley in Jiangsu Province of China (Du et al, 2015; Cheng et al, 2017). Seeds were provided by the Laboratory of Seed Science and Technology in Nanjing Agricultural University (Nanjing, Jiangsu Province, China).…”
Section: Methodsmentioning
confidence: 99%
“…The weight of imbibed seeds was recorded each 12 h to calculate the moisture content of seeds. Germination ability was observed every day to calculate germination percentage (GP) and seedling percentage (SP) (Du et al, 2015). Seeds were considered as germination when the radicle protruded (2 mm) through seed coat.…”
Section: Methodsmentioning
confidence: 99%
“…Consistently, RNAi-mediated knock-down of HvABA8 ′ OH1 leads to enhanced seed ABA level and dormancy ( Gubler et al, 2008 ). Studies in rice also indicated that the reduction of ABA level during imbibition of non-dormant seeds of rice is related mainly with increased expression of OsABA8ox (rice homologs of CYP707A ) genes ( Zhu et al, 2009 ; Du et al, 2015 ). These results suggest the significance of ABA catabolism in the regulation of ABA level and seed dormancy maintenance and release in the seeds of cereals such as rice and barley.…”
Section: Aba Regulates the Induction And Maintenance Of Seed Dormancymentioning
confidence: 99%
“…Consistently, comparative genomic analysis among barley, wheat, and rice identified HvGA20ox as a candidate gene regulating a seed dormancy QTL in barley ( Li et al, 2004 ). Likewise, the expression of the GA biosynthetic genes ( GA20ox and GA3ox2 ) is induced while that of GA inactivating genes ( GA2ox ) is repressed during imbibition of non-dormant rice and sorghum seeds, and this has been shown to be associated with increased level of bioactive GA ( Kaneko et al, 2002 ; Rodríguez et al, 2012 ; Du et al, 2015 ). Recent genetic studies in rice have identified OsGA20ox2 and OsGA2ox3 as candidate genes for controlling seed germination ( Ye et al, 2015 ; Magwa et al, 2016 ), and loss of function mutation in OsGA20ox2 leads to reduced seed GA level and enhanced dormancy ( Ye et al, 2015 ).…”
Section: Gibberellin Regulates Seed Dormancy and Germination In Cereamentioning
confidence: 99%